2021
DOI: 10.1186/s40738-021-00100-y
|View full text |Cite
|
Sign up to set email alerts
|

MAML1: a coregulator that alters endometrial epithelial cell adhesive capacity

Abstract: Background Abnormalities in endometrial receptivity has been identified as a major barrier to successful embryo implantation. Endometrial receptivity refers to the conformational and biochemical changes occurring in the endometrial epithelial layer which make it adhesive and receptive to blastocyst attachment. This takes place during the mid-secretory phase of woman’s menstrual cycle and is a result of a delicate interplay between numerous hormones, cytokines and other factors. Outside of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
(88 reference statements)
3
7
1
Order By: Relevance
“…51 Our recent study has revealed that knockdown of MAML1 in Ishikawa cells impairs their adhesive capacity. 28 This alteration in adhesion likely does not occur via alterations in the levels of the steroid hormone receptors PGR and ESR1 which is consistent with our observations in JAG1 siRNAtreated Ishikawa cells. Both JAG1 and MAML1 siRNA treatments only reduced the expression of HEY1, but not HES1, 28 indicating similar downstream effects of the Notchdependent pathway.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…51 Our recent study has revealed that knockdown of MAML1 in Ishikawa cells impairs their adhesive capacity. 28 This alteration in adhesion likely does not occur via alterations in the levels of the steroid hormone receptors PGR and ESR1 which is consistent with our observations in JAG1 siRNAtreated Ishikawa cells. Both JAG1 and MAML1 siRNA treatments only reduced the expression of HEY1, but not HES1, 28 indicating similar downstream effects of the Notchdependent pathway.…”
Section: Discussionsupporting
confidence: 90%
“…28 This alteration in adhesion likely does not occur via alterations in the levels of the steroid hormone receptors PGR and ESR1 which is consistent with our observations in JAG1 siRNAtreated Ishikawa cells. Both JAG1 and MAML1 siRNA treatments only reduced the expression of HEY1, but not HES1, 28 indicating similar downstream effects of the Notchdependent pathway. To investigate whether the regulation of receptivity markers by JAG1 was via the Notch-dependent or -independent pathway, MAML1 siRNA was transfected into Ishikawa cells to determine the effects on the expression of genes associated with receptivity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations